(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Charitable trust management system is designed mostly for orphanage home centers to achieve the orphan registration, adoption and maintenance. This platform can be used by Orphan Homes for useful interactions between your Adopters, Donors and Parents. Requirements can be updated and the Donors are notified about the new requirements. It provides an environment for adopters to find children. Charitable Trust Management System is the software used to store the adoption details, orphan details, donor details, donation details. To manage all these activities, we have developed this software. The charitable fund management system is built on the management side, so access is guaranteed only to managers. The goal of the paper is to establish connections between charitable trust and the donors/Adopter. It also maintains the records of the orphans in the Trust that allows online adoption of children and maintain the record of Adoption and keep track on the funds received and the expenditure of the trust.